Expert System for Diagnosing Diseases in Children Using the Bayes Theorem Method - Sri Hariani (Journal of Computer Science and Research (JoCoSiR), 2023)
The development of information technology is currently running very fast and plays an important role in various ways. Computers are an important part of improving information technology. The computer's ability to remember and store can be utilized without having to rely on barriers like those of humans, such as hunger, thirst or emotional states. By storing information and an adequate set of reasoning rules, it allows the computer to provide conclusions or make decisions that are of the same quality as the ability of an expert in a particular scientific field. One branch of computer science that can support this is an expert system. The making of this expert system application uses PHP as the programming language and MySQL as the database. This expert system application produces output in the form of the possibility of a child's illness based on the symptoms felt by the user. This system also displays the magnitude of the value of trust in these symptoms to the possibility of the patient's childhood illness. The magnitude of the trust value is the result of calculations using the Bayes Theorem method.